Estruturação e funcionamento de centros de documentação: o caso do centro de documentação da TV A Crítica - Santos, Sarah Emily Santos dos (Brasil, 2022)
It presents the results of the study carried out on the Documentation Center of TV A Critica and analyzes and reflects on its results. Its objective was to investigate the operational infrastructure of the Documentation Center of TV A Critica, in order to assess the scope of its contributions to the activities of this television station, its problem being the impacts of its performance on the activities of the Television News Writing Department of the station. Regarding its methodological course, considering the objectives of the study, the research was exploratory-descriptive, since the purpose was to obtain data and ample information about its operational infrastructures, to measure the contributions given to the activities of this station; as for the collection procedures, the research was bibliographical and field: in the first, carried out by consulting the literature in the areas of Librarianship and Information Science, the works and contents necessary to understand the theme, object and problem studied were selected , which were used in the analysis of the data and information collected and in the interpretation of the results achieved; and in the second, carried out through direct observation and application of a semi-structured interview, data and information about their operational infrastructures were collected; and with reference to the nature of the data collected in the field research, the research was quantitative-qualitative, since the study used objective data about the furniture and equipment of the Documentation Center and personal information, collected from the librarian responsible for its management, the which subsidized the assessment of its relevance to the performance of TV A Critica. As for the results of the study, it was found that its operational infrastructures were consistent with its functions and responsibilities, in particular with regard to furniture, equipment and the work team.